Review on interpersonal relationships and depression among shelter's children in Tehran/Iran - Ahangar, Katayoon; Juhari, Rumaya; Mansor, Mariani (Global Journals Inc., 2013)
This paper aims to review interpersonal relationship and depression among children living in shelters. The results revealed a negative significant correlation between various interpersonal relationship No significant difference in depression among male and female respondents. The review of this study will help guardians, social workers and psychologists to organize some intervention programmes so as to reduce depression among children living in Tehran’s shelters.